FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN TENAGA KESEHATAN TERHADAP KEBIJAKAN KESELAMATAN PASIEN DI INSTALASI RAWAT INAP - Handoko, Bobi; Fristasya, Andra; Firdaus, Muhammad; Mutiara, Sherly (LPPM Universitas Awal Bros, 2023)
Patient Safety is an important element to improve the quality of health services in the hospital, Patient safety is a system that makes patient care safer, including risk assessment, identification and management of patient risk, incident reporting and analysis, the ability to learn from incidents and their follow-up, and implementation of solutions to minimize risks and prevent injuries caused by errors due to carrying out an action or not taking action that should be taken The results of this study are the process in this study Influencing Health Worker Compliance with Patient Safety Policies in Inpatient Installations of Hospitals in Outpatient Admissions where the six patient safety targets in the hospital have been carried out quite well, the implementation of the six patient safety targets is also carried out both in the inpatient room and the polyclinic, However, from several interviews with patients, it was stated that the patient safety targets carried out in the hospital have not been fully met because there are still shortcomings such as the lack of effective communication methods to patients and not in accordance with the SKP. This study aims to find out about Influencing Health Workers' Compliance with Patient Safety Policies in Hospital Inpatient Installations. This type of research is qualitative with a descriptive analytical approach. This study was conducted on February 9 - June 30, 2023. The informants in this study numbered 5 people and this study used the Content Analysis model.